INTERPRETASI HAKIM TENTANG ANAK DI LUAR KAWIN PASCA PUTUSAN MAHKAMAH KONSTITUSI NOMOR 46/PUU-VIII/2010 TENTANG PENGUJIAN UU NOMOR 1 TAHUN 1974 TENTANG PERKAWINAN (Studi di Pengadilan Agama Purwokerto) - Mukhamad Farid (MIH Unsoed, 2015)
The religious court judges interpretation of the child outside the marriage after the Constitutional Court Decision No. 46 / PUU-VIII / 2010 on the review of Act 1 of 1974 in the Religious Navan and How the legal consequences of the Constitutional Court Decision No. 46 / PUU-VIII / 2010 on the review of Act No. 1 In 1974 in the Religious Purwokerto. This research method approach using Method approach taken in this study is a combination of socio-juridical field that uses primary data and secondary data from interviews with informants. Legal consequences of the Constitutional Court Decision No. 46 / PUU-VIII / 2010 on the testing of Law No. 1 In 1974 the Religious Court of Navan, which is stated in the decision of the Decision No. 1306 / Pdt.G / 2012 / PA.Pwt, that the reason behind the law to assert that illegitimate children were entitled to legal protection. The panel of judges to interpret the law or the interpretation of such cases and legal considerations have encouraged the necessity of providing protection and legal certainty to the status of a child born and the rights available to it, including against children born even though the validity of marriage is still disputed. Keywords: child outside marriage, interpretation and legal consequences.